AB0842 DISCOVERY OF ARTHRITIS IN PSORIASIS FOR EARLY RHEUMATOLOGIC REFERRAL (DAPPER): A CROSS-SECTIONAL STUDY. (2nd June 2020) - Van Hal, T.; Mulder, M.; Wenink, M.; Pasch, M.; Van den Reek, J.; De Jong, E.
Abstract : Background: One in three patients with psoriasis (Pso) will develop psoriatic arthritis (PsA) (1). When untreated, this can lead to disability and irreversible joint damage (2). Current screening methods are mostly based on questionnaires. These lack specificity and sensitivity (3, 4). Thus, a significant portion of PsA patients remains undetected. Objectives: Our main objective is to ascertain the prevalence of PsA in a cohort of Pso patient, treated at a dermatology outpatient clinic. Secondary, we wish to make a referral tool for dermatologist to detect patients suspected of PsA. Methods: A sample of 300 patients, stratified for current skin therapy (topical, systemic non-biologic, biologic), will be screened by a rheumatology resident for PsA signs and symptoms. When PsA is suspected, patients are referred to a rheumatologist for confirmation. We gather information about demography, treatment (past and current) and comorbidity. On top of that, we gather data on disease specifics (age of onset, disease duration, severity). We store biomaterials and DNA. Eventually, all these data will be used to form a more specific prediction model which can be used at the dermatology department for more efficient referral. Results: We will present preliminary data of the first 100 patients. In this cohort, we found 14 patients with known PsA. 10 patients were suspected of (previously undiagnosed) PsA, and were referred to a rheumatology clinic. Three cases were confirmed, and 4 are still under analysis. This makes the prevalence of PsA in Pso 17-21%. Of these three new cases, one was treated with topical therapy only, one was treated with a biologic, and one received targeted therapy. In the patients with PsA, we found a higher amount of men. On top of that, we found a trend towards more intensive therapy. This may be due to indication bias, were the presence of arthritis may lead to a more aggressive treatment. Interestingly, 2 of the 3 previously undiagnosed PsA patients were treated with a biological for their skin symptoms. Conclusion: Preliminary data of the DAPPER study reveal that the prevalence of confirmed PsA in Pso patients is 17%. If all suspected PsA are confirmed, this rises to 21%. Even under systemic biologic treatment, arthritis can still be active. References: [1]Mease PJ, Gladman DD, Papp KA et al. Prevalence of rheumatologist-diagnosed psoriatic arthritis in patients with psoriasis in European/North American dermatology clinics. J Am Acad Dermatol 2013;69(5):729-735. [2]Kane D, Stafford L, Bresnihan B, FitzGerald O. A prospective, clinical and radiological study of early psoriatic arthritis: an early synovitis clinic experience. Rheumatology (Oxford) 2003;42(12):1460-1468. [3]Coates LC, Aslam T, Al BF et al. Comparison of three screening tools to detect psoriatic arthritis in patients with psoriasis (CONTEST study). Br J Dermatol 2013;168(4):802-807. [4]Haroon M, Kirby B, FitzGerald O. High prevalence of psoriatic arthritis in patients with severe psoriasis with suboptimal performance of screening questionnaires. Ann Rheum Dis 2013;72(5):736-740. Disclosure of Interests: Tamara van Hal Speakers bureau: Lilly Eli, Michelle Mulder: None declared, Mark Wenink: None declared, Marcel Pasch: None declared, Juul Van den Reek Speakers bureau: Abbvie, Eli Lilly, Elke De Jong Grant/research support from: Abbvie, Janssen Pharmaceutica, Consultant of: AbbVie, Janssen Pharmaceutica, Novartis, Eli Lily and Company, Celgene, and Leo Pharma., Speakers bureau: AbbVie, Janssen Pharmaceutica, Novartis, Eli Lily and Company, Celgene, and Leo Pharma.